2021
DOI: 10.1111/ced.14634
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Hedgehog signalling molecules in microcystic adnexal carcinoma

Abstract: Background. Microcystic adnexal carcinoma (MAC) is a rare skin neoplasm that has not been characterized on a molecular basis. Aim. To assess expression profiles of Hedgehog (HH) signalling molecules in MAC and control tumours. Methods. Immunohistochemistry was performed for Sonic Hedgehog (SHH), Indian Hedgehog (IHH), Patched 1 (PTCH1) and Smoothened (SMO) on patient MAC tissue (n = 26) and control tumour tissue, including syringoma (SyG; n = 11), trichoepithelioma (TE; n = 11) and basal cell carcinoma (BCC; n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…These data were consistent with another study in which sequencing indicated a mutation of TP53 with loss of CDKN2A and CDKN2B in metastatic MAC [74]. Another study reported that, unlike basal cell carcinoma, Hedgehog signaling was not significantly altered in MAC [75]. Considering its lack of UV signature and since no oncogenic mutation was identified in one third of the cases in the largest study to date, more studies are required, including the detection of gene fusions, to reveal the genomic landscape of MAC.…”
Section: Microcystic Adnexal Carcinomasupporting
confidence: 91%
“…These data were consistent with another study in which sequencing indicated a mutation of TP53 with loss of CDKN2A and CDKN2B in metastatic MAC [74]. Another study reported that, unlike basal cell carcinoma, Hedgehog signaling was not significantly altered in MAC [75]. Considering its lack of UV signature and since no oncogenic mutation was identified in one third of the cases in the largest study to date, more studies are required, including the detection of gene fusions, to reveal the genomic landscape of MAC.…”
Section: Microcystic Adnexal Carcinomasupporting
confidence: 91%